The Role of Passive legs Raising Position in Hypovolemic Shock: A Case Report and Review of the Literature - Rahmawati, Ira; Dilaruri, Ade; Sulastyawati; Supono (Universitas STRADA Indonesia, 2021)
Background: Hypovolemic shock can be catastrophic rapidly unless recognized and treated promptly. Although gastrointestinal loses might be the cause of hypovolemic shock in the elderly, it rarely causes a change in the blood gas analysis results.Purpose: This study aimed to report a case of a 75-year-old male with signs of hypovolemic shock caused by gastrointestinal loses and discuss the effect of passive leg raising procedure as an early nursing intervention in patients presenting with shock.Methods: The method used in this paper is a case study. The subject in this study is a 75-year-old male presenting to our Emergency Room with signs of shock which was caused by gastrointestinal problems. Passive leg raising or also known as modified Trendelenburg Position was performed as the patient presenting with low blood pressure. The results of physical dan laboratory investigation, as well as the nursing and medical therapies were presented, analyzed and discussed based on the recent literature.Results: There was an increase in the Mean Arterial Pressure (MAP) after the intervention was given for five minutes followed by fluid resuscitation with 1000 ml of warm Normal Saline. The patient responded well to the intervention given in the ED and was sent to the Intermediate Ward for further treatments.Conclusion: Passive leg raising might be beneficial to be performed in patients with hypovolemic shock as it increases the venous blood return the heart.